p,p'-DDT induces testicular oxidative stress-induced apoptosis in adult rats - Neila Marouani; Dorsaf Hallegue; Mohsen Sakly; Moncef Benkhalifa; Khémais Ben Rhouma; Olfa Tebourbi (BMC, 2017)
Abstract Background The 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (p,p'-DDT) is a known persistent organic pollutant and male reproductive toxicant. The present study is designed to test the hypothesis that oxidative stress mediates p,p'-DDT-induced apoptosis in testis. Methods Male Wistar rats received an intraperitoneal (ip) injection of the pesticide at doses of 50 and 100mg/kg for 10 consecutive days. The oxidative stress was evaluated by biomarkers such lipid peroxidation (LPO) and metallothioneins (MTs) levels. Antioxidant enzymes activities was assessed by determination of superoxide dismutase (SOD), catalase (CAT) and hydrogen peroxide (H2O2) production. In addition, glutathione-dependent enzymes and reducing power in testis was evaluated by glutathione peroxidase (Gpx), glutathione reductase (GR), glutathione S-transferase (GST) activities and reduced and oxidized glutathione (GSH - GSSG) levels. Apoptosis was evaluated by DNA fragmentation detected by agarose gel electrophoresis. Germinal cells apoptosis and the apoptotic index was assessed through the TUNEL assay. Results After 10 days of treatment, an increase in LPO level and H2O2 production occurred, while MTs level, SOD and CAT activities were decreased. Also, the Gpx, GR, GST, and GSH activities were decreased, whereas GSSG activity was increased. Testicular tissues of treated rats showed pronounced degradation of the DNA into oligonucleotides as seen in the typical electrophoretic DNA ladder pattern. Intense apoptosis was observed in germinal cells of DDT-exposed rats. In addition, the apoptotic index was significantly increased in testis of DDT-treated rats. Conclusions These results clearly suggest that DDT sub-acute treatment causes oxidative stress in rat testis leading to apoptosis.